FEEDING DETERRENT ACTIVITY OF ANDROGRAPHOLIDE AGAINST COTTON BOLLWORM , HELICOVERPA ARMIGERA HüBNER (LEPIDOPTERA : NOCTUIDAE) - Wawan Hermawan (BIOTIKA Jurnal Ilmiah Biologi, 2002)
In laboratory choice and no-choice tests, andrographolide was tested against the 4thinstar larvae of the cotton bollworm (CBW), Helicoverpa armigera using cabbage leaf disc. Each test was repeated 5 times. No-choice test showed that andrographolide was less effective in feeding suppression against CBW. In choice test, andrographolide significantly suppressed feeding at high dose of 400mg/leaf disc. Key words : Helicoverpa armigera, andrographolide, feeding deterrent.